2017
DOI: 10.1111/jir.12356
|View full text |Cite
|
Sign up to set email alerts
|

The Mandarin Chinese version of the Beach Centre Family Quality of Life Scale: development and psychometric properties in Taiwanese families of children with developmental delay

Abstract: This study showed that the Mandarin Chinese version of the BCFQOL is reliable and valid for Taiwanese families of children with DD. The instrument could be applied to assess FQOL in families of children with DD who are receiving EI in order to evaluate family services and supports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
8
15
0
Order By: Relevance
“…There are numerous studies that explicitly address the limitations of not taking into account more than one of the parents, which shows that there is an ethical concern in this regard [35,39,42,43,45,46,[53][54][55]60,75,82,84]. Gardiner and Iarocci [91] indicate that in the future, research on the FQoL should include the voices of the different members of the family.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous studies that explicitly address the limitations of not taking into account more than one of the parents, which shows that there is an ethical concern in this regard [35,39,42,43,45,46,[53][54][55]60,75,82,84]. Gardiner and Iarocci [91] indicate that in the future, research on the FQoL should include the voices of the different members of the family.…”
Section: Discussionmentioning
confidence: 99%
“…Even though-as pointed out-numerous papers have in recent years have focused on the construction, validation, or study of tools to measure FQoL [14,20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], authors agree on the need to continue to devote efforts to optimizing their internal structures and revising how they work in different populations in different contexts (socio-demographic, cultural, etc.) [25,29,31,39,40]. In this sense, after applying the CdVF-E < 18 and the CdVF-E > 18 scales for 5 years, we deemed it appropriate to revise them both and identify their internal structures for research [44,60] and intervention purposes in the Spanish context [61].…”
Section: Introductionmentioning
confidence: 99%
“…The BCFQOL scale is one of the most used scales with different samples from different cultures ( Park et al, 2003 ; Poston et al, 2003 ; Verdugo et al, 2005 ; Zuna et al, 2009 ; Balcells-Balcells et al, 2011 ; Meral et al, 2013 ; Parpa et al, 2016 ; Chiu et al, 2017 ; Schlebusch et al, 2017 ; Waschl et al, 2019 ; Balcells-Balcells et al, 2020 ; Kyzar et al, 2020 ). Psychometric properties were examined and showed good reliability and construct validity ( Hoffman et al, 2006 ), for example, in China, Hu et al (2012) findings supported the five-dimensional factor structure, and Chiu et al, 2017 results showed good fit indices for the five-factor model (first-order) with correlations between the five latent variables ranging from 0.70 to 0.93. In addition, similar findings with good psychometric properties in other different studies, such as, in the US ( Boehm et al, 2015 ), Turkey ( Meral et al, 2013 ), and Saudi Arabia ( Alnahdi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers used the total score as an indicator of the FQOL satisfaction level based on the overall mean score for all 25 items (e.g., Boehm et al, 2015 ; Chiu et al, 2017 ). According to Boehm et al (2015) , the use of the overall mean to examine predictors was justified because subscales were highly correlated.…”
Section: Introductionmentioning
confidence: 99%